Chest pain and coronary endothelial dysfunction after recovery from COVID‐19: A case series. Issue 4 (8th April 2022) - Shah, Samit M.; Odanovic, Natalija; Kunnirickal, Steffne; Feher, Attila; Pfau, Steven E.; Spatz, Erica S.
Abstract: Endothelial cell damage related to coronavirus disease 2019 (COVID‐19) has been described in multiple vascular beds, and many survivors of COVID‐19 report chest pain. This case series describes two previously healthy middle‐aged individuals who survived COVID‐19 and were subsequently found to have symptomatic coronary endothelial dysfunction months after initial infection. Abstract : COVID‐19 can lead to the development of vascular endothelial dysfunction, which may be present in coronary arteries, and can be uncovered by invasive coronary physiology testing.